Has Australia’s Road to Workplace Partnership Reached a Dead End? - Townsend, K.; Wilkinson, A.; Burgess, John; Brown, Kerry (Kluwer Law International, 2013)
Over the last fifteen years, a number of developed countries have pursued an agenda seeking to develop more collaborative management-union arrangements often labelled as partnerships. This article reviews the Australian road to partnerships by situating it within the context of developments in the UK and New Zealand. In 2009, Australia’s then Deputy Prime Minister and Minister for Workplace Relations, Julia Gillard, suggested that Australian Industrial Relations were about to undergo a shift towards a new model of workplace interaction that included more collaboration and partnerships. We argue that rather than a substantial shift, this approach can be viewed as an evolution from the Accord years, disrupted for a period by the Howard Government. However, unlike similar regulatory regimes in the United Kingdom and New Zealand, the Australian Government has done little to entrench a system of partnerships at the workplace level. This article assesses the extent to which collaboration and partnership in Australia’s modern IR system provides a roadmap to a new Australian IR landscape, or whether the failure of policy-makers to act has led to a dead-end for Australian partnerships. The practical implications of this agenda for the conduct of industrial relations are considered.